Utilizing Black Soldier Fly Larvae for Sustainable Organic Waste Management and Urban Farming: Efficiency, Challenges, and Scalability - Dwi Retno Mulyanti; M Reza Alfikri; Ayu Putri Ana; Ester Juliana Sitohang; Khitara Aldila Chandra; Dwi Noviyanto; Agung Catur Wibowo (Jurnal Teknologi dan Manajemen Industri Terapan, 2025)
This study investigates the potential of Black Soldier Fly (BSF) larvae in managing organic waste through rapid decomposition and nutrient-rich compost production. The primary objective was to evaluate the efficiency of BSF larvae in waste reduction and compost quality, particularly within urban environments, and to explore their scalability in urban waste management systems. The methodology involved controlled experiments to measure bioconversion rates at varying larval densities, temperature, and moisture levels. The compost produced by BSF larvae was analyzed for key nutrients, including nitrogen, phosphorus, and potassium. The results demonstrated that BSF larvae effectively reduced organic waste by up to 86% within a few days, outperforming traditional composting methods. The compost produced was rich in essential nutrients, making it suitable for urban farming. Factors such as optimal larval density, temperature, and moisture content were crucial for maximizing decomposition efficiency and compost quality. However, the study also identified several challenges, including space constraints, public perception, and the logistical difficulties of scaling BSF larvae systems in urban areas. In conclusion, this research highlights the potential of BSF larvae as a sustainable solution for organic waste management, compost production, and urban farming. The findings contribute to the growing knowledge on sustainable waste management and urban agriculture, offering insights into integrating BSF larvae systems into existing waste management frameworks. Future research is needed to address scalability challenges and optimize the operational efficiency of BSF larvae systems in urban environments.